JESUS’ MOVEMENT : A HEALING FELLOWSHIP - Kalluveettil, Paul (Journal of Dharma, 1999)
Now some teachers of the law were sitting there, thinking to themselves, ’why does this fellow talk like that? He is blaspheming! Who can forgive sins but God alone?’ Immediately Jesus knew in his spirit that this was what they were thinking in their hearts, and he said to them, ’why are you thinking these things? Which is easier; to say to the paralytic, ’your sins are forgiven’, or to say, ’get up, take your mat and walk?’ but that you may know that the son of man has authority on earth to forgive sins... ’, he said to the paralytic, ’I tell you, get up, take your mat and go home.’ He got up, took his mat and walked out in full view of them all. 111is amazed everyone and they praised God, saying, "we have never seen anything like this!" (Mark 2:1-12).